ANALYZING THE IMPACT OF ORGANIC MANURES ON SOIL MICROBIAL PARAMETERS FOLLOWING OKRA-BROCCOLI CROPPING PATTERN - VISHAW VIKAS,; JAG PAUL SHARMA, (The Bioscan, 2020)
A study was conducted at OFR Centre of SKUAST -Jammu to find out the impact of organic manures on soil microbial and enzymatic health following Okra-Broccoli cropping pattern. Significant results in microbial biomass carbon were obtained with highest Microbial Biomass Carbon (MBC) value 45.65 μg g -1 was observed in T8 in okra and 47.49 μg g -1 in broccoli. Highest to lowest value observed was 2.80 μg g-1 (T 8 ) to 2.63 μg g -1 (T 1 ) in okra and 3.20 μg g -1 (T 8 ) to 2.89 μg g -1 (T 1 ) in broccoli. Highest Dehydrogenase (DHG) value 122.55 μg TPF g -1 soil day- 1 was observed in T8 in okra and 123.41 μg TPF g -1 soil day-1 in broccoli. Highest to lowest value observed was 12.86 μg PNP g -1 soil day-1 (T 8 ) to 12.04 μg PNP g -1 soil day-1 (T 1 ) in okra and 13.10 μg PNP g -1 soil day-1(T 8 ) to 12.26 μg PNP g -1 soil day-1 (T 1 ) in broccoli. Microbial Biomass Nitrogen (MBN) and Acid Phosphatase (ACP) values were found to be non-significant as minor variations in treatments were observed as compared to control. In the experiment, the most effective treatment was found to be T8 comprising of Vermicompost + Poultry Manure @ 5.00 + 1.45 t ha -1 .